Motivations for the use of games in coping and emotional regulation - Cahill, Tiernan J.; Cummings, James J.; Wertz, Erin (Frontiers in Communication, 2025)
IntroductionThis study explores motivations for the use of video games in coping, using the twin theoretical lenses of mood management and stress response theory, as well as how individual differences in motivational orientation moderate emotional regulation. The role of genres in selective exposure and the extent to which this overlaps with individual motivations for play are also addressed.MethodsAn exploratory survey (N = 348) was conducted to gather data on respondents’ personalities, gameplay habits, motivations, genre preferences, coping strategies, and emotional states.ResultsGameplay as coping was found to be quite widespread, and associations were found between this behavior and respondents’ motivations for gaming in general, as well as with individual differences related to immersion. Motivational orientations towards narrative involvement, social interaction, and escapism were likewise associated with using games to cope with stress, while the regulatory effects of gameplay were also found to be moderated by players’ orientation towards autonomy and exploration.DiscussionThese findings suggest that individual differences in immersive tendencies and motivational orientations play a crucial role in determining when and how video games serve as effective tools for emotional regulation and coping with stress.